Ответ:
1)у=(-2)²-2×(-2)-3
у=4+4-3
у=5
2)у=(-1)²-2(-1)-3
у=1+2-3
у=0
3)у=0²-2×0-3
у=-3
4)у=1²-2×1-3
у=1-2-3
у=-4
5)у=2²-2×2-3
у=4-4-3
6)у=(-1/2)²-2×(-1/2)-3
у=1/4+1-3
у=-1 3/4
7)у=(1/2)²-2×1/2-3
у=1/4-1-3
у=-3 3/4
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1)у=(-2)²-2×(-2)-3
у=4+4-3
у=5
2)у=(-1)²-2(-1)-3
у=1+2-3
у=0
3)у=0²-2×0-3
у=-3
4)у=1²-2×1-3
у=1-2-3
у=-4
5)у=2²-2×2-3
у=4-4-3
у=-3
6)у=(-1/2)²-2×(-1/2)-3
у=1/4+1-3
у=-1 3/4
7)у=(1/2)²-2×1/2-3
у=1/4-1-3
у=-3 3/4